Endoscopic laser treatment of vascular anomalies of the upper gastrointestinal tract. Issue 12 (December 1985) - Bown, S G; Swain, C P; Storey, D W; Collins, C; Matthewson, K; Salmon, P R; Clark, C G
Abstract : Vascular anomalies of the gastrointestinal tract are an important source of both acute and chronic blood loss. They present difficult management problems as they are often multiple, involving more than one part of the gastrointestinal tract, and may give rise to bleeds of increasing frequency and severity over a period of many years. We present the results of endoscopic argon and Nd YAG laser treatment of 18 patients with documented recurrent, severe haemorrhage from vascular lesions of the upper gastrointestinal tract with follow up of up to five years. Four patients with hereditary haemorrhagic telangiectasia, five with single angiodysplasias and three with multiple angiodysplasias have had their transfusion requirements reduced to minimal levels after one or more courses of laser treatment. Two of these have required no blood for over two years despite previous total requirements of 52 and 129 units of blood. Four patients were submitted to surgery (two in whom the laser failed to control haemorrhage and two who did not have immediate access to laser therapy at the time of severe bleed). Two of these, however, bled again soon afterwards. Two patients are still undergoing courses of laser therapy although have already shown reductions in transfusion requirements. Both lasers were effective. The Nd YAG laser appears to produce better long term results as its greater penetration makes it possible to ablate the main areas of vascular ectasia in the submucosa, although it does have a slightly higher risk of causing haemorrhage in the first few days after treatment.